Combining PD-L1 blockade with immunogenic cell death induced by AIE photosensitizer to improve antitumor immunity. (December 2022) - Li, Jianqing; Dai, Jun; Zhuang, Zeyan; Meng, Zijuan; Hu, Jing-Jing; Lou, Xiaoding; Xia, Fan; Zhao, Zujin; Tang, Ben Zhong
Abstract: Immunogenic cell death (ICD) is considered an effective death mode to trigger immune response. However, the currently available efficient ICD inducers are quite limited. Endoplasmic reticulum (ER) stress is known as the precursor of ICD, which can be directly triggered by reactive oxygen species in situ . Herein, a novel photosensitizer ( α -Th-TPA-PIO) based on phosphindole oxide, featuring aggregation-induced emission (AIE) is designed and prepared, which possesses good ability of hydroxyl radicals (HO ) generation. Besides, α -Th-TPA-PIO can selectively accumulate in ER and trigger ER stress under white light irradiation, further leading to effective ICD. Combining with anti-programmed death-ligand 1 ( anti -PD-L1), the synergistic effect of photodynamic therapy (PDT) and immune checkpoint blockade can achieve a significantly enhanced inhibition effect on the growth of tumors and simultaneously provoke a systemic antitumor immune response. Notably, by adopting this therapeutic strategy to bilateral and metastatic tumor models, the growth of both primary and distant subcutaneous tumors can be successfully suppressed, and metastatic tumor can also be inhibited to some degree. Taken together, this work not only provides a novel ICD photoinducer based on PDT, but also brings about a useful immunomodulatory strategy to realize superior antitumor effect.